Investigating the role of potassium channel KAT1 in NO mediated stomatal closure - Ördög, Attila; Wodala, Barnabás; Horváth, Ferenc (Acta Biologica Szegediensis, 2008)
KAT1, a hyperpolarization-activated, inward-rectifying K+ channel is one of the main transportersparticipating in guard cell volume regulation. The voltage-dependence of KAT1 channel is regulated by several intracellular factors, including pH, ATP and cGMP (Hoshi 1995). NO, a regulator of a branch of ABA signalling pathways in guard cells decreases the Ca2+-dependent inward potassium current by increasing the cytosolic free Ca2+ concentration. Based on the Ca2+-independent feature of KAT1 homotetramer protein, we aimed to examine the direct and indirect effects of NO on this channel.